Tela de Babel: Historicidade e Transições no Mercado Audiovisual - Silva, Dirceu Lemos da (2018)
We are facing a new media context with the increase of audiovisual content offering, audiences’ hyper segmentation and the price decrease of connecting devices, which are even more convergent. These new digital technologies allow users to be at the same time active producers, programmers and distributors of audiovisual content. Based on the historicity of the main technologies for capturing, reproducing and transmitting image and sound of cinema and TV, the present study analyses how the audiovisual ubiquity in infinite screens has led to a rapid alteration in the television business models. The TV, which was for decades the most powerful and influent mass media, is now forced to reinvent itself and split revenues with new disruptive players emerged from the Internet, such as Netflix. The work was based on media studies supported by exploratory and bibliographical research methodology, as well as documentary analysis. The frame of reference is based on the theoretical background of authors such as Henry Jenkins, Nicholas Negroponte and Guillermo Orozco who advocate the coexistence of the old and the new media. In the Babel of the screens, television becomes one among many other displays.